Intraspecific Trait Variability of a Diatom and a Dinoflagellate Along a Salinity Gradient - Orizar, Iris Delos Santos; Lewandowska, Aleksandra M. (Frontiers in Marine Science, 2022)
The phytoplankton community is a highly diverse group of microscopic, photosynthetic organisms responsible for 50% of the global primary production. The predicted shift in ocean salinity due to climate change threatens phytoplankton, resulting in compositional shifts and changing biodiversity patterns. This study investigates intraspecific multi-trait variability and plasticity of Alexandrium ostenfeldii and Skeletonema marinoi along a salinity gradient. Multiple traits were measured for five strains of each species grown at six salinity levels (0, 5, 15, 20, 30, and 35 psu) and combined in the principal component analysis. Cell size contributed 52% to the total variation in traits composition and significantly differed between species. The trait plasticity of A. ostenfeldii was significantly higher than S. marinoi, and the highest trait plasticity was observed at 15 psu in both species. In addition to morphological traits, A. ostenfeldii was characterized by high plasticity of cellular carbon content and a higher C:P ratio at low salinity levels. Overall, the results suggest a high variation in traits plasticity between phytoplankton strains, emphasizing the importance of intraspecific diversity to maintain ecosystem functions under changing environmental conditions.